Our experience with the management of penile fracture: a single institutional prospective observational study in eighteen patients over a two-year period - Sengupta, Soumish; Basu, Supriya; Ghosh, Kadambari; Sengupta, Subhrajyoti (International Surgery Journal, 2021)
Background: Penile fracture is a not an unusual encounter in urological emergency. The condition results from disruption of the tunica albuginea which envelops the corpora cavernosa as a result of any condition which leads to the sudden rise of intra-cavernosal pressure. The study was designed to analyse the clinical spectrum and complication of penile fracture. Methods: This is a prospective observational study undertaken from April, 2019 to March, 2021on 18 patients. The demographic profile of all the patients, aetiology of penile fracture, management strategies and pre-operative sexual functions were documented. Erectile function was evaluated using international index of erectile function (IIEF). Results: Seventeen out of 18 patients (94.44%) gave a history of injury during sexual intercourse. Out of the seventeen patients with history of injury following sexual intercourse, only 9 (52.94%) were married. 15 (93.75%) had disruption of the tunica albuginea in the ventrolateral position with 10 patients (66.66%) on the right side. Patients were followed up in the OPD after 2 weeks and then at 6 month and 1-year intervals. At 12 months postop, none of the patients complained of sexual inactivity. Average time to return to sexual activity was 3.2 months. Two patients complained of penile curvature >20 degree. Six patients complained of penile nodule at the site of repair. Conclusions: Penile fracture is a urological emergency which is primarily diagnosed clinically. Prompt diagnosis and surgical exploration gives good outcome in terms of preservation of sexual function.